A study on the outdoor landscape design for the people with disabilities (Pwds) - Mohd Mardzi, Ardi Herman (2008)
There are numbers of issues regarding lack of facilities in providing the user-friendly environment for the people with disabilities (PWDs). These issues were raised by various societies of the disabled person including the deaf, physically disabled such as wheelchair users as they need to access to these public spaces such as recreational areas. Outdoor environment is often described as environments which consider the typical need of a people, at the external part of a building. There are always landscape elements, hardscape, street furniture, public facilities, gardens, and open spaces or courtyards made for the people to utilize. These are the examples of elements in our environment, in which it fulfills the need of people and interact with the outdoor living environment. This research aims to determine the need of the PWDs and the aged, for their outdoor living environment as well as the suitable facilities to be provided for them in religious building and public toilet. it is hoped that the case study in Syria will benefit us in generating more ideas of improving the current condition of religious building, public toilet and the public realms in Malaysia and other parts of religious countries.